30.2k views
5 votes
If f(x) =
(x+3)/(4), what is the equation for f–1(x)?

f–1(x) = 4(x + 3)

f–1(x) = 4x - 3

f–1(x) = 4(x - 3)

f–1(x) = 4x + 3

2 Answers

4 votes

Answer:

Choice b is correct.

The inverse of function f(x)=x+3/4 is 4x-3

Explanation:

Given function is:

f(x)=x+3 / 4

We have to find the inverse of f(x)

Put f(x)=y in above equation

y = x+3 / 4

We have to separate x from above equation.

Multiplying 4 on both sides of above equation,we have

4y=(x+3)

Adding -3 to both sides of above equation,we have

4y-3=x+3-3

x=4y-3

Replacing y to x and x to f⁻¹(x) we have

f⁻¹(x)=4x-3

This is our required result.

The inverse of the function f(x)=x+3/4 is 4x-3

User Giorgos Betsos
by
6.1k points
2 votes

Answer:

option (b) is correct

inverse of function
f(x)=(x+3)/(4) is 4x+3

Explanation:

Given function
f(x)=(x+3)/(4)

We have to find the inverse of given function.

Let f(x) = y then taking inverse both sides, we get


f^(-1)(y)=f^(-1)(f(x))\\\\\ f^(-1)(y)=x

Substitute , x and f(x) in given equation, we get,


f(x)=(x+3)/(4) \Rightarrow ((f^(-1)(y))+3)/(4)

Now solve for
(f^(-1)(y)) , we get,


(f^(-1)(y))+3=4y


(f^(-1)(y))=4y-3

Thus, inverse of function
f(x)=(x+3)/(4) is 4x+3

Thus, option (b) is correct.

User Abhijeet Navgire
by
6.2k points